Power and influence in organizations : new empirical and theoretical perspectives - Schriesheim, Chester. (Research in management, 2025)
1. What Do Managers Do When Subordinates Just Say, ¿No?¿ An Analysis of Incidents Involving Refusal to Perform Downward Requests Bennett J. Tepper 000 2. Power and Influence in the Context of Organizational Innovation: Empirical Findings Diana E. Krause 000 3. The Use of Power Bases in Different Contexts: Arguments for a Context-Specific Perspective Diana E. Krause and Eric Kearney 000 4. Proactive Influence Tactics and Leader Member Exchange Gary Yukl and John W. Michel 5. Power and Politics in Relay CEO Succession Richard J. Gentry, Charlice Hurst, and Wei Shen 000 6. To Influence or Adjust: A Dynamic Model of Person-Group Fit Chad A. Higgins and Tomoki Sekiguchi 000 7. Conflict Among Subordinates and Conflict-Handling Styles as Predictors of Managers¿ Anticipated Power-Sharing: An Experimental Investigation Claudia C. Cogliser and Chester A. Schriesheim